2020
DOI: 10.15252/embj.2019104013
|View full text |Cite
|
Sign up to set email alerts
|

Stable expansion of high‐grade serous ovarian cancer organoids requires a low‐Wnt environment

Abstract: High‐grade serous ovarian cancer (HGSOC) likely originates from the fallopian tube (FT) epithelium. Here, we established 15 organoid lines from HGSOC primary tumor deposits that closely match the mutational profile and phenotype of the parental tumor. We found that Wnt pathway activation leads to growth arrest of these cancer organoids. Moreover, active BMP signaling is almost always required for the generation of HGSOC organoids, while healthy fallopian tube organoids depend on BMP suppression by Noggin. Fall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
433
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(435 citation statements)
references
References 48 publications
2
433
0
Order By: Relevance
“…Indeed, data from a large genome-wide association study (GWAS) in EOC were indicative for a significant downregulation of the Wnt pathways-agonist WNT4 in ovarian tumors [ 61 ]. Moreover, a recent study has demonstrated that the inactivation of the Wnt/β-catenin pathway is required for maintaining stemness and preventing the differentiation of organoid cultures derived from high-grade serous ovarian cancer (HGSOC) patients, and that HGSOC progresses more aggressively in an environment free of Wnt [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, data from a large genome-wide association study (GWAS) in EOC were indicative for a significant downregulation of the Wnt pathways-agonist WNT4 in ovarian tumors [ 61 ]. Moreover, a recent study has demonstrated that the inactivation of the Wnt/β-catenin pathway is required for maintaining stemness and preventing the differentiation of organoid cultures derived from high-grade serous ovarian cancer (HGSOC) patients, and that HGSOC progresses more aggressively in an environment free of Wnt [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microarray data. GEO (http://www.ncbi.nlm.nih.gov/geo) [24] is is a common database for storing chips, second generation sequencing, and other high-throughput sequencing data.. Two gene expression datasets (GSE146553 [25] and GSE124766 [26] ) were downloaded from GEO.By annotating the information, we rst obtain the genetic symbol which converted from the probe.The GSE146553 dataset included 26 OC tissue samples and 3 normal samples. The GSE124766 included 8 OC samples and 3 normal samples.…”
Section: Methodsmentioning
confidence: 99%
“…Organoids can be established from pathological samples and provide powerful tools to study diseases ex vivo although the culture conditions often need optimizing [69,78,95,[102][103][104][105][106][107][108][109][110][111] ( Table 4). A common benign condition is endometriosis where ectopic foci of the endometrium containing both glands and stroma are found in the peritoneal cavity, ovary, and cervix.…”
Section: Endometriosis and Endometrial Hyperplasiamentioning
confidence: 99%
“…Growth and long-term expansion has now been achieved by using media with low WNT and active BMP signaling to maintain stem cells in the cultures (Table 4) [106]. These conditions are also required for the stable growth of another model of HGSOC that were derived by the stable triple knockdown of TP53, PTEN, and RB in fallopian tube organoids [106]. Similarly, organoids can be derived from different stages of endometrial neoplasms that capture the phenotypic and genetic heterogeneity (Table 4).…”
Section: Carcinomas Of the Frtmentioning
confidence: 99%